LIG - an interactive video system for tablets - Morais, Cleber Matos de; Leitão, Guilherme Pontes; Diniz, Amanda Carvalho; Teixeira, Marianna Cruz; Machado, Augusto Ygor; Tanaka, Misaki (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
The portable digital devices’s market has grown in recent years. The devices’ interaction possibilities have become more sophisticated with the multitouch capacitive screens. The touch used to control the narrative flow of those devices poses challenges to communicators, programmers, designers, and developers in general. Products and current concepts cannot meet all the possible and incessant demand that portable interactive media, especially tablets, cause. Thus, the main purpose of this paper is to present the development of the Interactive Language Gestures (LIG) and its playback system designed to be used in digital videos interaction in order to expand videographic hypertext narratives for tablets. The LIG system encompasses the application (AppLIG), the language for creating hypertext videos (XLIG), the audio stream transition language to keep videos uninterrupted (XSLIG), and finally, the production and assembly diagram (DLIG). The LIG system allows to store and display navigation between videos without the need for graphical interfaces